Classification criteria for Sjögren's syndrome: we actually need to definitively resolve the long debate on the issue. Issue 4 (22nd December 2012) - Vitali, Claudio; Bootsma, Hendrika; Bowman, Simon J; Dorner, Thomas; Gottenberg, Jacques-Eric; Mariette, Xavier; Ramos-Casals, Manuel; Ravaud, Philippe; Seror, Raphaele; Theander, Elke; Tzioufas, Athanasios G
Abstract : A new approach for the classification of patients with Sjögren's syndrome (SS) has been recently proposed. Although these new criteria substantially differ from the American European Consensus Group criteria, which have represented the gold standard for the last decade, when compared with each other the two sets show a high statistical degree of agreement. However, the fact that two different criteria to classify patient with SS could be available may introduce some additional difficulties in the scientific communication, making cohorts of patients selected by using different methods less than completely equivalent, and the results of epidemiological studies and therapeutic trials not entirely comparable. Consequently, to reach a consensus agreement on universally accepted classification criteria for SS seems to be a very desirable objective.